Sanksi Riddah Perspektif Maqasid Al-Shariâah - Azizah, Imroatul (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: Riddah (apostasy), in the classical literatures of Islamic Jurisprudence, is categorized as a jarimah al-hudud (criminal act) with death penalty as the punishment. The fundamental issue is that the threat of the death penalty is only based on a single prophetic tradition, while it should be determined by the absolute and valid texts. It means that the death penalty is rooted to an absolute legal argumentation (qatâi al-dalalah), while, there is none of the verses of al-Qurâan which discusses about punishment for the perpetrator of apostasy. Otherwise, al-Qurâan absolutely guaranteesthe freedom of religion and belief. This research uses maqasid al-shariâah (purposes of Islamic law)as an approach to see the purpose, spirit, and essential valueof the text to be a foundation and method in Islamic legal reasoning. The results of the research are: first, adopting what has been stipulated in al-Qurâan textually and formally without appreciating its purpose and wisdom is not wise; second, apostasy, which is a kind of a private matter between a servant and his God, should not be categorized as a jarimah al-hudud but as a jarimah taâzir (undefined crime). In certain condition, however, apostasy could be charged by a maximum penalty (death penalty) if it is accompanied by other crimes and is worthyto be sentenced based on a judgeâs argumentation.Keywords: Apostasy, sanctions, maqasid al-shariâahÂ Abstrak: Riddah dalam literatur fiqih klasik dikategorikan sebagai jarimah hudud, dan diancam dengan hukuman mati. Persoalan yang mendasar adalah ancaman hukuman mati tersebut hanya berdasarkan hadis ahad, padahal hudud dikonsepsikan sebagai jarimah dan hukuman yang telah ditentukan secara pasti oleh nass. Berarti hudud meniscayakan dalil yang qatâi al-dalalah, sedangkan dalam al-Qurâan tidak ada satu ayat pun yang membahas hukuman duniawi untuk pelaku riddah, sebaliknya al-Qurâan justru memberikan jaminan kebebasan beragama dan berkeyakinan secara mutlak. Maqasid al-shariâah dipilih sebagai pendekatan untuk melihat bagaimana tujuan, ruh, dan nilai-nilai esensial shariâat dijadikan landasan dan patokan utama dalam penentuan hukum Islam. Dengan pendekatan maqasid al-shariâah, diperoleh kesimpulan bahwa bukanlah sikap yang bijak ketika mengadopsi apa yang ditetapkan dalam nass secara literal dan formal legalistik tanpa mengapresiasi tujuan serta hikmah terdalam dari hukum tersebut. Riddah yang merupakan persoalan pribadi antara hamba dengan Tuhan-Nya, tidak selayaknya dikategorikan sebagai jarimah hudud. Namun sebagai jarimah taâzir, riddah bisa dikenakan hukuman maksimal (mati) jika disertai dengan kejahatan lain yang menurut hakim harus dijatuhi hukuman tersebut.Kata Kunci: Riddah, sanksi, maqasid al-shariâah